2010
DOI: 10.1159/000279304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Electroencephalographic Mean Frequency in Depressed Elderly Subjects

Abstract: Background: An analysis of cortical activity by electroencephalogram (EEG) may show different patterns in depressed and normal individuals. Objectives: Our study aimed (1) to compare the total mean frequency (TMF) and mean EEG frequency per bands (MFB) in depressed and healthy elderly individuals, and (2) to verify the effect of exercise as an additional treatment for major depressive disorder (MDD; according to DSM-IV) via an assessment of depressive symptoms, TMF and MFB. Methods: This research was divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
1
19
0
2
Order By: Relevance
“…The increase in right alpha power observed in the control group could be related to a decrease in EEG activity, also observed in elderly individuals with cognitive impairment (38). Several studies have used EEG parameters to investigate treatment response (30,39), since they could be helpful to predict the outcome of antidepressant treatment (39) or for the evaluation of treatment (30). Although alpha power is the most frequently investigated EEG variable, other bands (e.g., theta) and other variables (e.g., EEG mean frequency) have also been utilized with this purpose.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The increase in right alpha power observed in the control group could be related to a decrease in EEG activity, also observed in elderly individuals with cognitive impairment (38). Several studies have used EEG parameters to investigate treatment response (30,39), since they could be helpful to predict the outcome of antidepressant treatment (39) or for the evaluation of treatment (30). Although alpha power is the most frequently investigated EEG variable, other bands (e.g., theta) and other variables (e.g., EEG mean frequency) have also been utilized with this purpose.…”
Section: Discussionmentioning
confidence: 89%
“…Although alpha power is the most frequently investigated EEG variable, other bands (e.g., theta) and other variables (e.g., EEG mean frequency) have also been utilized with this purpose. Recently, our laboratory observed that depressed elderly individuals showed an increase in EEG mean frequency after 6 months of exercise training (30). Iosifescu et al (39) found that frontal relative theta power at baseline was significantly lower in responder than in non-responder subjects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Estudos longitudinais anteriores também observaram redução significativa dos sintomas depressivos nos idosos com DM após o exercício físico 12,27,28 . Apesar da maioria dos estudos realizar intervenções somente com TA 10,29 , os poucos estudos que utilizaram TF também mostraram resultados positivos para os sintomas depressivos 14,15 .…”
Section: Discussionunclassified
“…The effect of physical exercise is associated with the reduction of depression symptoms, increase of functional capacity, improvement of quality of life and alterations of cortical activity in depressed older adults 3,25,[30][31][32][33][34][35] . Strength and aerobic training contribute to the increased response to treatment (50% reduction of depression symptoms) and remission (reduction in depression scales to a cut-off score of asymptomatic classification).…”
Section: Depressionmentioning
confidence: 99%